2016
DOI: 10.3389/fmicb.2016.00586
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Patterns of Pseudomonas spp. Isolated from the River Danube

Abstract: Spread and persistence of antibiotic resistance pose a severe threat to human health, yet there is still lack of knowledge about reservoirs of antibiotic resistant bacteria in the environment. We took the opportunity of the Joint Danube Survey 3 (JDS3), the world's biggest river research expedition of its kind in 2013, to analyse samples originating from different sampling points along the whole length of the river. Due to its high clinical relevance, we concentrated on the characterization of Pseudomonas spp.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 30 publications
8
28
0
1
Order By: Relevance
“…The occurrence of P. aeruginosa was found to be higher in males, inpatients in age group >60 years and in surgery department, which is same as reported by Marzoqi et al,10 . This might be due to prolonged hospitalization and other associated co-morbidities in these age groups.…”
supporting
confidence: 89%
“…The occurrence of P. aeruginosa was found to be higher in males, inpatients in age group >60 years and in surgery department, which is same as reported by Marzoqi et al,10 . This might be due to prolonged hospitalization and other associated co-morbidities in these age groups.…”
supporting
confidence: 89%
“…Isolates were also very resistant to Amoxicilin/clavulanic acid-30µg 26 (81.3%) and Cephalexin-10 µg 24 (75.0%). Similar studies by Kittinger, et al [27] also showed that Pseudomonas is highly susceptible to gentamycin. A study from Garba, et al [28] also confirms high susceptibility of Pseudomonas to ofloxacin and gentamycin as well as its high resistance to Amoxicilin/Clavulanic acid (Augmentin).…”
Section: Results Of Total Heterotrophic Bacteria Andsupporting
confidence: 74%
“…These opportunistic pathogens are host to several intrinsic and acquired resistance genes which they can also exchange with other gram negative bacteria (Juan Nicolau and Oliver, 2010). Hence, Pseudomonas is responsible for the occurrence and spread of several important carbapenemases (β-lactamases) (Kittinger et al, 2016). P. aeruginosa has high environmental tolerance, impermeable outer membrane, forms biofilms and has a several siderophores and pigments that allow it to evade the innate immune system (Fair and Tor, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Other species like P. putida and P. fluorescens cause a variety of infections in clinical settings (Kittinger et al, 2016). Contaminated catheters and other medical devices transmit these pathogens causing bacteraemia, sepsis, pneumonia, urinary tract infections (UTIs), burn and wound infections, etc (Peleg and Hooper, 2010).…”
Section: Introductionmentioning
confidence: 99%